2021
DOI: 10.1016/j.jenvman.2020.111907
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of human migration and city lockdowns on specific air pollutants during the COVID-19 outbreak: A spatial perspective

Abstract: The outbreak of COVID-19 continues to bring unprecedented shock to mankind's socioeconomic activities, and to the wider environment. China, as the early epicenter of the pandemic, locked down one-third of its cities in an attempt to prevent the rapid spread of the virus. Human migration patterns have subsequently been radically altered and many regions have seen perceived improvements in air quality during the lockdowns. This study empirically examines the relationship between human migration and air pollution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Air quality improvement is an indirect environmental benefit of lockdown policies in response to the pandemic ( Braga et al, 2020 ; Depellegrin et al, 2020 ; Wang and Su, 2020 ; Zeng and Bao, 2021 ). An annual peak period of returning home and returning to workplaces normally emerges after the Spring Festival holiday.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Air quality improvement is an indirect environmental benefit of lockdown policies in response to the pandemic ( Braga et al, 2020 ; Depellegrin et al, 2020 ; Wang and Su, 2020 ; Zeng and Bao, 2021 ). An annual peak period of returning home and returning to workplaces normally emerges after the Spring Festival holiday.…”
Section: Discussionmentioning
confidence: 99%
“…The observed decrease in population migration has been attributed to the pandemic outbreaks and traffic restriction policies ( Lau et al, 2021 ). Nonetheless, cities are inherently heterogeneous entities ( Zeng and Bao, 2021 ). Our study found that the classification of city scale, pollution level, and population mobility is consistent with the characteristics of the cluster mappers of the local Moran's I.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The performed studies showed that the level of primary pollution causes secondary pollution, which in turn exacerbates the environmental situation (Zheng et al, 2020). Thus, theoretical air pollution models estimating human migration have been developed for comparing the results of eld research (Zeng & Bao, 2021).…”
Section: Introductionmentioning
confidence: 99%